Wealth Obsession and Disillusionment: The Teachings of Islam and the Perceptions of EM Forster - Md. Munibur Rahman (Indonesian Journal of Islamic Literature and Muslim Society)
Wealth obsession poses a significant threat to civilization, humanity, and peace on personal, national, and global scales. Stemming from excessive greed, this obsession renders people's lives distressingly difficult and persistently problematic, fueling an insatiable hunger for power and possessions. In his essay 'My Wood', English writer EM Forster vividly illustrates the psychological impact of wealth on individuals, elucidating why and how people become fixated on accumulating boundless riches and the inevitable consequences they face upon achieving them. His insights resonate deeply with the teachings of Islam. It is evident that many individuals pursue wealth relentlessly without discerning the boundaries they should adhere to. Awareness of these boundaries could curb their pursuit once reached. Are they guided by a known destination or boundary, or are they merely chasing a mirage? Both Islamic teachings and EM Forster's observations address this quandary, offering guidance on overcoming wealth obsession and leading a tranquil, morally sound life.